2011
DOI: 10.2478/v10153-011-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response and Immunologic Memory in Medical Personnel Vaccinated with Hepatitis B Vaccine

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…Aside from those factors, patients with concomitant disease usually have a complicated and inconstant status due to diverse pathogenesis. Although some researches found no association between comorbidity and seroprotection 36 37 , comorbidity may be a significant element decreasing the efficacy of hepatitis B vaccine from this analysis and others 23 27 , which could bring immunity disturbance. However, the detailed mechanisms between the poor response to hepatitis B vaccine and adults suffering from concomitant disease are still incompletely understood.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Aside from those factors, patients with concomitant disease usually have a complicated and inconstant status due to diverse pathogenesis. Although some researches found no association between comorbidity and seroprotection 36 37 , comorbidity may be a significant element decreasing the efficacy of hepatitis B vaccine from this analysis and others 23 27 , which could bring immunity disturbance. However, the detailed mechanisms between the poor response to hepatitis B vaccine and adults suffering from concomitant disease are still incompletely understood.…”
Section: Discussioncontrasting
confidence: 53%
“…A previous meta-analysis in 2002 observed many factors influencing response to hepatitis B vaccine, especially a decrease response to recombinant HBV vaccine at higher ages11, which suggested that earlier vaccination should be prioritized for prevention at the population level. However, in the last decade, numerous emerging reports, which focused on the seroprotection rate of hepatitis B vaccine in adults12131415161718192021222324252627282930313233343536373839404142434445464748, are still inconclusive to immunize what adults are the most appropriate in order to increase the seroprotection rate. Factors influencing immunologic response to hepatitis B vaccine in adults have been inconsistently examined in existing studies.…”
mentioning
confidence: 99%
“…There have been studies demonstrating that postvaccinal immunity against hepatitis B is not only humoral, but it has been detected that immunologic memory determined by HBsAg -specific T-lymphocytes persists long time after vaccination in recipients with serum antibodies <10 mIU/ ml. 20 We have found better immune response after application of hepatitis B vaccine among female gender compared to male gender, as per most of the authors. Men have a reduced response to conventional hepatitis B vaccines.…”
Section: Discussionsupporting
confidence: 59%
“…17,18 Fifth, improved control and implementation of hepatitis B virus vaccine. [19][20][21][22][23] Sixth, the results from the study could be influenced by disorders in medical statistics.…”
Section: Discussionmentioning
confidence: 99%